Technique and drive in Iberê Camargo - Rosenfield, Lenora Lerrer (PORTO ARTE: Revista de Artes Visuais, 2016)
The article reports convivial experience with artist Iberê Camargo (Restinga Seca, 1914 - Porto Alegre, 1994), pointing his apprenticeship training and workshop practice, emphasizing the expression through a painting driven by intense dramatic drive.